Nexus between COVID-19 and periodontal disease - Sukumar, Kanchana (J Int Med Res, 2021)
Over the past several decades, studies have demonstrated the existence of bi-directional relationships between periodontal disease and systemic conditions. Periodontitis is a polymicrobial and multifactorial disease involving both host and environmental factors. Tissue destruction is primarily associated with hyperresponsiveness of the host resulting in release of inflammatory mediators. Pro-inflammatory cytokines play a major role in bacterial stimulation and tissue destruction. In addition, these cytokines are thought to underlie the associations between periodontitis and systemic conditions. Current research suggests that increased release of cytokines from host cells, referred to as the cytokine storm, is associated with disease progression in patients with coronavirus disease 2019 (COVID-19). An intersection between periodontitis and pulmonary disease is biologically plausible. Hence, we reviewed the evidence linking COVID-19, cytokines, and periodontal disease. Plaque control is essential to prevent exchange of bacteria between the mouth and the lungs, reducing the risk of lung disease. Understanding these associations may help identify individuals at high risk and deliver appropriate care at early stages.